PENGUATAN KADER GIZI MELALUI EDUKASI DAN PELATIHAN GIZI SEIMBANG SEBAGAI UPAYA PENCEGAHAN STUNTING DI DESA TEGALSARI - Larasaty, Nurina Dyah; Handarsari, Erma; Puji Astuti, Andari; Purnomo, Yunda Yutisa (Gapenas Publisher, 2025)
Tegalsari Village, Karanggede Subdistrict, Boyolali Regency, is predominantly inhabited by residents with lower-middle economic status, which affects dietary patterns and nutritional intake, especially among toddlers. Initial data indicated low maternal knowledge about balanced nutrition, minimal participation in posyandu activities, and the absence of community nutrition cadres to provide ongoing education. In response, the Community Service (PKM) team implemented the program “Strengthening Community Nutrition Cadres for Stunting Prevention,” which included education on balanced nutrition and the impacts of stunting, training on preparing balanced menus based on local wisdom, and the formation of competent nutrition cadres.The results showed a significant increase in participants’ knowledge, with the average post-test score of 80.00 rising from a pre-test score of 59.33. Most participants now fall into the “good” knowledge category, while those with “poor” knowledge decreased to 0%. The established nutrition cadres are able to disseminate information and healthy nutrition practices sustainably, as well as assist families in preparing balanced menus and monitoring child growth.This program is expected to enhance the community’s understanding of the importance of balanced nutrition, encourage healthy eating habits, and promote active participation in stunting prevention. Strengthening the capacity of cadres has the potential to improve program effectiveness holistically, ensuring that stunting prevention can be implemented independently and sustainably at the community level.